Learning Circumference and Area of Building with Video Media for Fourth Class Students of Elementary School - Made Dewanda Sulaksana; Kadek Yudiana; alexander Hamonangan Simamora (Jurnal Ilmiah Sekolah Dasar, 2021)
The lack of use of interesting learning media makes students less active during the online learning process. To overcome this, it is necessary to develop a media in the learning process. This study aims to produce a video of learning mathematics on the topic of perimeter and area of flat shapes for fourth grade elementary school students that have been tested for acceptability. This study uses the type of research and development (Research and Development). This study uses the ADDIE model. The subjects in this study were 2 subject content experts, 2 media experts and design experts, and 2 practitioner experts to determine the validity of instructional video media. while the object of research is the validity of learning video media. This study uses a questionnaire method and rating scale instrument as a means of data collection. Based on the research results, 88% and 92% are scores obtained from subject matter content experts with good and very good predicates, 87% and 92% are scores obtained from design experts with good and very good predicates, 88% and 88% are scores obtained from media experts with good predicates, and 90% and 90% are scores obtained from expert practitioners with very good predicates. Based on these results, it can be concluded that the development of learning video media on the topic of circumference and area of flat shapes for fourth grade elementary school students is declared valid and feasible to use in the learning process.